Produksi Cabai Merah (Capsicum annuum L.) dari Benih yang Diinduksi Medan Magnet 0,2 mT dan Diinfeksi Jamur Fusarium sp. - Rochmah Agustrina; Herta M. Manullang; Bambang Irawan; Sri Wahyuningsih; Sumardi Sumardi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2020)
As one of the horticultural plants that has important economic value, the cultivation of red chili (Capsicum annuum L.) is often constrained by the attack of Fusarium sp., which can cause losses due to decreased production. Induction of the magnetic field on the plant is known to be able to increase growth, development, and production in various plants. In this research, we studied the production of chili grown from seeds exposed to a 0.2 mT magnetic field and then infected with Fusarium sp. The study was conducted factorial using a completely randomized design with 2 factors. The first factor is the exposure of a 0.2 mT magnetic field to the seeds consisting of controls, without exposure to a magnetic field (M0), magnetic field exposure for 7 minutes 48 seconds (M7), and 15 minutes 30 seconds (M15). The second factor is Fusarium sp. infection on seeds that have been exposed to a magnetic field for 60 minutes by immersion of the seeds with spore suspension of Fusarium sp. with the density of 1 x 107 conidia/ml (F60), and without Fusarium sp. infection (F0). Each treatment unit was repeated 5 times. The data obtained were analyzed for variance at α = 5% followed by the least significant difference test using the Fishers Test at α = 5%. The results of data analysis showed that the interaction of 0,2 mT magnetic field exposure and infection of Fusarium sp. in chili seeds significantly affect the stomata index, the fruiting rate, and the number of fruit but do not affect the content of total chlorophyll, carbohydrate, as well as the number of flowers. The highest fruiting rate and number of fruits obtained from the treatment result of 0.2 mT magnetic field exposure for 15 minutes 36 seconds without Fusarium sp. infection (M15F0). Infection of Fusarium sp. in these seeds (M15F60) reduce the fruiting rate and the number of fruit but it is not significant and even almost similar with the fruiting rate and the fruit number of the plant growth from control treatment (M0F60). Key words: magnetic field, Fusariumsp., seed, and production.